Intensive care unit nurses' perceptions of patient participation in the acute phase of chronic obstructive pulmonary disease exacerbation: an interview study. (18th April 2012) - Kvangarsnes, Marit; Torheim, Henny; Hole, Torstein; Öhlund, Lennart S.
<x xml:space="preserve">Abstract</x> kvangarsnes m., torheim h., hole t. & öhlund l.s. (2012) Intensive care unit nurses' perceptions of patient participation in the acute phase of chronic obstructive pulmonary disease exacerbation: an interview study. Journal of Advanced Nursing69(2), 425–434. doi: 10.1111/j.1365‐2648.2012.06021.x Abstract Aim. To report a study conducted to explore intensive care unit nurses' perceptions of patient participation in the acute phase of chronic obstructive pulmonary disease exacerbation. Background. An acute exacerbation is a life‐threatening situation, which patients often consider to be extremely frightening. Healthcare personnel exercise considerable power in this situation, which challenges general professional notions of patient participation. Design. Critical discourse analysis. Methods. In the autumn of 2009, three focus group interviews with experienced intensive care nurses were conducted at two hospitals in western Norway. Two groups had six participants each, and one group had five (N = 17). The transcribed interviews were analysed by means of critical discourse analysis. Findings. The intensive care nurses said that an exacerbation is often an extreme situation in which healthcare personnel are exercising a high degree of control and power over patients. Patient participation during exacerbation often takes the form of non‐involvement. The participating nurses attached great importance to taking a sensitive approach when meeting patients. The nurses experienced challenging ethical dilemmas. Conclusion. This study shows that patient participation should not be understood in universal terms, but rather in relation to a specific setting and the interactions that occur in this setting. Healthcare personnel must develop skill, understanding, and competence to meet these challenging ethical dilemmas. A collaborative inter‐professional approach between physicians and nurses is needed to meet the patients' demand for involvement.